2014
DOI: 10.1111/sms.12222
|View full text |Cite
|
Sign up to set email alerts
|

Reporting doping in sport: National level athletes' perceptions of their role in doping prevention

Abstract: This paper qualitatively explores national level athletes' willingness to report doping in sport.Following ethical approval, semi-structured interviews were conducted with nine national level athletes from rugby league (n = 5) and track and field athletics (n = 4). Thematic analysis established the main themes within the data. Contextual differences existed around the role that athletes perceived they would play if they became aware of doping. Specifically, track and field athletes would adopt the role of a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…The first phase involved familiarization and immersion in the data through manual transcription of the interviews and reading and rereading through the whole dataset. This process can facilitate the comprehension of the complexity of the dataset (Smith & Caddick, ; Whitaker et al., ). Initial thoughts about the data were recorded during this phase, prior to the more formal and systematic stages of coding.…”
Section: Methodsmentioning
confidence: 99%
“…The first phase involved familiarization and immersion in the data through manual transcription of the interviews and reading and rereading through the whole dataset. This process can facilitate the comprehension of the complexity of the dataset (Smith & Caddick, ; Whitaker et al., ). Initial thoughts about the data were recorded during this phase, prior to the more formal and systematic stages of coding.…”
Section: Methodsmentioning
confidence: 99%
“…Whitaker et al [108] conducted semi-structured interviews on athletes' perceptions of their role in doping prevention. The study concluded that prevention programs would need to focus on changing the broader group and community norms on doping.…”
Section: Preventionmentioning
confidence: 99%
“…Implementation of whistleblowing requires a set of measures adapted to the national context. The identification of the elements responsible for the efficiency of whistleblowing methods, the consistency of measures to protect whistleblowers remain specific to each country and even to the groups of athletes practicing certain sports (Whitaker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, however, there are several differences regarding the assumption of warning behaviour, depending on the sport branch. While athletes would notify the authorities if they had information about doping cases, rugby players would adopt a code of silence and would not report the case (Whitaker, Backhouse, & Long, 2014). Against this background, a number of recommendations are formulated on the content of educational programs to be organized so that athletes, coaches and other people involved in the sporting phenomenon are best informed about the risks of consumption of doping substances, take responsibility on preventing this behaviour and engaging in whistleblowing.…”
Section: Education Programs For Ethics and Integrity In Sportmentioning
confidence: 99%